Relative optical transmittance of aqueous ‏extracts of the middle layer of the fruits of ‏the Nile acacia plant - Rayan. Ali, Abdalla (International Journal of Scientific World, 2025)
This study dealt with determining the relative optical transmittance of ‏aqueous extracts of Nile acacia fruitsThis is after preparing aqueous ‏extracts at certain concentrations after dilution operations to determine ‏the first concentration, and the concentration was set at 100 Celsius, and ‏the permeability was measured using a Spectrophotometer deviceWith a ‏wavelength of 600 nanometers for yellow or brownish solutions, ‏transmittance is estimated using optical measurements of aqueous ‏extracts of the sample. It blocks and reflects the light passing through it ‏with the concentration of the sample in the extract. The light that is ‏absorbed or reflected through the solution is directly proportional to the ‏sample concentration, i.e. the light that passes through it is proportional. ‏Inversely with the concentration of the sample in the solutionAfter ‏measuring the intensity of light transmitting from the device, we ‏performed other mathematical operations to find the relative optical ‏transmittance, which was very high at 99.75%. This indicates that the ‏solution is regular and that the ions or particles that make it up transmit ‏light through it.